Odpowiedzi

2010-01-27T21:02:39+01:00
A)4xjednatrzecia-(jednatrzecia+6)=czterytrzecie-jednatrzecia-6=1-6=-5
b)(a+4b)-(5+2a)-(3b-5)= a+4b-5-2a-3b+5= -a+b= -(-0,1)+0,2= 0,1+0,2= 0,3
c)(-a²+2ab-1)+(a²-4ab+5)= -a²+2ab-1+a²-4ab+5= 2ab+4= 2(jednaczwarta×2)+4=
2×dwieczwarte+4= 1+4= 5

I to by było na tyle ;D
2010-01-27T21:21:33+01:00
A) 4x-(x+6)+4 dla x= ¹₃
4x⅓-(⅓+6)+4=
1⅓-(6⅓)+4=1

b)(x²+1)-(x²-2)+10 dla x=2,2
( 2,2²+1)-(2,2²-2)+10=
(4,84+1)-(4,84-2)+10=
5,84 - 2,84 + 10=
= 13

c)(a+4b)-(5+2a)-(3b-5) dla a=-0,1 i b=0,2
(-0,1+4x0,2)-(5+2x(-0,1))-(3x0,2-5)
(-0,1+0,8)-(5-0,2)-(0,6-5)=
0,7-4,8-(-4,4)=
0,7-4,8+4,4=
0,3

d)(-a²+2ab-1)+(a²-4ab+5) dla a=¹₄ i b =2
((-¼²)+2(¼x2)-1)+((¼²)-4(¼x2)+5=
(¹/₁₆+1-1)+(¹/₁₆-2+5)=
¹/₁₆ + ( ¹/₁₆+3)=
¹/₁₆ + 3¹/₁₆=
3²/₁₆ = 3 ⅛